Rattlesnake Kinship: Indigeneity, Disability, Animality - Vivian Delchamps (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: Indigeneity; Animal Studies; Kinship; Hopi Nation; Rattlesnakes; American History